2022
DOI: 10.3389/fendo.2022.965379
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic signatures responding to PKM2 activator TEPP-46 in the hyperglycemic human renal proximal epithelial tubular cells

Abstract: Pyruvate kinase M2 (PKM2), as the terminal and last rate-limiting enzyme of the glycolytic pathway, is an ideal enzyme for regulating metabolic phenotype. PKM2 tetramer activation has shown a protective role against diabetic kidney disease (DKD). However, the molecular mechanisms involved in diabetic tubular have not been investigated so far. In this study, we performed transcriptome gene expression profiling in human renal proximal tubular epithelial cell line (HK-2 cells) treated with 25 mM high D-glucose (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…It has also been shown to facilitate angiogenesis of extracellular maxtrix PKM2 in cancer cells [ 82 ]. The findings from another study, which identified important prospective transcriptome indicators and biological pathways in hyperglycemic HK-2 cells responsive to the PKM2 activator TEPP-46, underscore the need for more investigation into the signaling mechanisms regulating EGFR and metabolic stress [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to facilitate angiogenesis of extracellular maxtrix PKM2 in cancer cells [ 82 ]. The findings from another study, which identified important prospective transcriptome indicators and biological pathways in hyperglycemic HK-2 cells responsive to the PKM2 activator TEPP-46, underscore the need for more investigation into the signaling mechanisms regulating EGFR and metabolic stress [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TEPP-2 was shown to restore hyperglycemia-induced glomerular and tubular metabolic phenotypes, further inhibiting fibrotic progression in DKD. Wang et al cultured HK-2 cells under sustained high glucose exposure (7 days) with (case group) or without (control group) the addition of TEPP-46 for another 1 day and analyzed the genome-wide transcriptome data from the case and control groups (7). Four extremely downregulated DE genes (HSPA8, HSPA2, HSPA1B, and ARRB1) and three extremely upregulated differentially expressed genes (GADD45A, IGFBP3, and SIAH1) are involved in decreased endocytosis (hsa04144) and the enhanced p53 signaling pathway (hsa04115), respectively.…”
mentioning
confidence: 99%
“…Pyruvate kinase muscle isozyme M2 (PKM2) forms both dimers and tetramers ( 7 ). In proliferation, the dimeric state of PKM2 promotes anabolism, such as in the polyol pathway, pentose phosphate pathway, and uronic acid pathway ( 7 ). In contrast, the tetrameric state of PKM2 promotes ATP synthesis and catabolism.…”
mentioning
confidence: 99%
See 2 more Smart Citations